Processos de aquecimento na alta atmosfera estelar: emissão coronal em raio-x e emissão cromosférica em CaII - Souza Neto, Luiz Pinheiro de (2006)
In the present work we study the processes of heating in the high stellar atmosphere, with base in an analysis of behavior of the cromospheric and coronal emission for a sample of single stars classified as giant in the literature. The evolutionary status of the stars of the sample was determined from HIPPARCOS satellite trigonometric parallax measurements and from the Toulouse Genéve code. In this study we show the form of behavior of the CaII emission flux in spectral lines H and K F(CaII) and the X-ray emission flux in function of the rotation, number of Rossby Ro and depth in mass of the convective envelope. In this analysis we show that while the cromospheric activity is dominated clearly by a physical process of heating associated with the rotation, like a magnetic field produced by dynamo effect, the coronal activity seems to be influenced for a mechanism independent of the rotation. We show also that the effective role of the depth in massa of the convective envelope on the stellar activity has an important effect in the responsible physical process for the behavior of the activity in the atmosphere of the stars.